The importance of visual acuity screening in dental education amongst undergraduate dental students: a straightforward method - Pindoria, Jaya; Abela, Stefan; Maguire, Matthew; Sherriff, Martyn; Bister, Dirk (Frontiers in Dental Medicine, 2024)
Background Visual acuity plays a pivotal role in a dental professional's daily performance and screening the students' field of vision in their early formative years ensures successful undergraduate programmes. Aims To compare near and distance visual acuity and stereopsis in first-year and final-year dental students and investigate students' perception of their vision. Method This was a cross-sectional study involving 100 KCL first- and final-year dental students who underwent assessment of their vision and completed a self-perception questionnaire. Near visual acuity was assessed using a standardised near vision test chart, distance visual acuity using COMPlog (Clinical Vision Measurement Systems Ltd, London, UK) computerised software and stereopsis using the Frisby Stereotest. Based on the Mann–Whitney test, no statistical differences were found between the first-year and final-year students’ near and distance visual acuity, nor in stereopsis difference at a significance level of α = 0.05. The null hypothesis was accepted. Results 84% of first-year students and 94% of final-year students attained the highest binocular near visual acuity score of 0.50M. Distance visual acuity scores showed a median ETDRS (Early Treatment Diabetic Retinopathy Study) Letters score 94 in the first-year group and 95 in the final-year group. 8% of students were found to have correctable refractive errors in distance visual acuity. The majority of students across both year groups were able to discern 20 s arc of the smallest disparity. The final-year students reported worrying about their eyesight significantly more than the first-year students. Conclusions No statistically significant differences were found in near and distance visual acuity, and stereopsis, between first-year and final-year dental students. However, 8% of students were identified with undiagnosed, correctable refractive errors. The importance of students' vision in clinical dentistry is highlighted, and regular eye examination is recommended.